MONUMEN PALAGAN TUMPAK RINJING DAN INGATAN MASYARAKAT KABUPATEN PACITAN ATAS REVOLUSI FISIK 1949 - Azifambayunasti, Azril (Universitas Negeri Malang, 2021)
The Palagan Tumpak Rinjing Monument is a symbol of preserving memory for the events of the 1949 Physical Revolution in Pacitan Regency. In general, this research aims to describe the historical narrative behind the construction of the Palagan Tumpak Rinjing Monument and collective memory of 1949 Physical Revolution symbolized in the monument. This study uses a qualitative method, in which the researcher collects information through interview with relevant informants by purposive sampling technique and studies of some supporting literature. The results showed that the events behind the construction of the Palagan Tumpak Rinjing Monument was local people's resistance to the Dutch troops during Physical Revolution in several parts of Indonesia. However, the monument that was built three decades after the incident displays the icons of General Soedirman and B. S. Riyadi. It then affects the formation of collective memory of the people who tend to forget the role of local fighters and see the big man as central figures who contributed to heroic events around them. Monumen Palagan Tumpak Rinjing adalah simbol melestarikan memori untuk peristiwa Revolusi Fisik 1949 di Kabupaten Pacitan. Secara umum, penelitian ini bertujuan untuk menggambarkan narasi sejarah di balik pembangunan Monumen Palagan Tumpak Rinjing dan memori kolektif Revolusi Fisik 1949 yang dilambangkan dalam monumen. Studi ini menggunakan metode kualitatif, di mana peneliti mengumpulkan informasi melalui wawancara dengan informan yang relevan dengan teknik purposive sampling dan studi dari beberapa literatur pendukung. Hasil penelitian menunjukkan bahwa peristiwa di balik pembangunan Monumen Palagan Tumpak Rinjing adalah perlawanan masyarakat setempat terhadap pasukan Belanda selama Revolusi Fisik di beberapa bagian Indonesia. Namun, monumen yang dibangun tiga dekade setelah kejadian menampilkan ikon Jenderal Soedirman dan B. S. Riyadi. Ini kemudian mempengaruhi pembentukan memori kolektif dari orang-orang yang cenderung melupakan peran pejuang lokal dan melihat orang besar sebagai tokoh sentral yang berkontribusi pada peristiwa heroik di sekitar mereka.